2022
DOI: 10.1097/md.0000000000029990
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes of using the nonirradiated and irradiated allograft for anterior cruciate ligament (ACL) reconstruction: A systematic review update and meta-analysis

Abstract: Background: This study was a systematic review comparing the clinical outcomes of using the nonirradiated and irradiated allograft for anterior cruciate ligament (ACL) reconstruction. Methods: A comprehensive literature search was conducted using multiple databases, including Medline, Embase, and Cochrane. All databases were searched from the earliest records through August 2019 using the following Boolean operators: irradiated AND nonirradiated AND ACL AND allograft. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…For example, in the study by Wasserstein et al [61] who reported, on seven studies addressing patients aged less than 25 years, higher failure rates of allografts versus autografts, only two studies assessed autograft versus non-irradiated allograft, and in this analysis no statistically significant difference in graft failure was seen. Liu et al [66] showed, in a recent systematic review, that non-irradiated allografts are superior to irradiated allografts based on improved knee joint functional scores and decreased failure rate. Also, Wang et al [67] performed a meta-analysis looking at autograft versus non-irradiated and irradiated allografts.…”
Section: Allograftmentioning
confidence: 99%
“…For example, in the study by Wasserstein et al [61] who reported, on seven studies addressing patients aged less than 25 years, higher failure rates of allografts versus autografts, only two studies assessed autograft versus non-irradiated allograft, and in this analysis no statistically significant difference in graft failure was seen. Liu et al [66] showed, in a recent systematic review, that non-irradiated allografts are superior to irradiated allografts based on improved knee joint functional scores and decreased failure rate. Also, Wang et al [67] performed a meta-analysis looking at autograft versus non-irradiated and irradiated allografts.…”
Section: Allograftmentioning
confidence: 99%
“…There is extensive but contradicting evidence comparing graft rupture rates between allograft and autograft. Allografts are thought to have higher rupture and reoperation rates, with an up to sixfold increased risk of failure when compared to autograft, especially in young and active patients [ 18 , 58 , 63 , 72 , 96 , 126 ]. Sterilization using radiation, especially with doses greater than 20 kGy, has been implicated as a likely cause due to unfavorable biomechanical effects on the tissue [ 66 , 115 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 58 ]. Thus, although several systematic reviews and meta-analyses comparing autograft to non-irradiated or fresh frozen allograft have reported no significant differences in failure rates in older patients [ 24 , 134 , 136 ], the use of allograft in young and active individuals remains unacceptably high and is therefore not recommended in this age group [ 18 , 50 , 58 , 63 , 72 , 126 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of hydroxyapatite-based scaffolds for hard tissue applications is gaining importance as a reliable option to bone replacements [1][2][3][4][5]. Due to the shortage of donors worldwide [6] and the threat of infection [7], autograft and allograft are not practical options for bone substitutes. Abundantly available and environmentally friendly hydroxyapatite has biological similarities to bone tissue [8][9][10][11], making it an attractive option for hard tissue engineering and biomedical engineering research [12].…”
Section: Introductionmentioning
confidence: 99%